THE EFFECTIVENESS OF PRESENTATION, PRACTICE, AND PRODUCTION TO IMPROVE STUDENTS' WRITING SKILLS ON DESCRIPTIVE TEXT - Stefani, Adira Nabila; Hidayat, Hamdan; Gaffar, Muhammad Andriana (TELL - US JOURNAL, 2025)
This study aims to test the effectiveness of the PPP (Presentation, Practice, and Production) method in improving descriptive text writing skills among eighth-grade students at SMP Negeri Bandung. The PPP method is implemented through three stages: Presentation, Practice, and Production. In the Presentation stage, the teacher delivers the material in a structured manner. In the Practice stage, students engage in guided writing practice. Whereas in the Production stage, students produce writing independently. This study uses a quantitative approach with a pre-experimental design, employing the one-group pretest-posttest technique. Data were collected through descriptive writing tests before and after the implementation of the PPP method. The research results show a significant improvement in students' writing skills after the implementation of the PPP method. The average pretest score of 56.94 increased to 68.85 on the posttest. Statistical analysis using the paired t-test showed a significance value (p < 0.05), which means that the PPP method is effective in improving students' descriptive writing skills. Based on these findings, it is concluded that the PPP method is an effective teaching strategy and is recommended for use in teaching descriptive text writing.